Isolation and characterization of CAC antenna proteins and photosystem I supercomplex from the cryptophytic alga Rhodomonas salina - Kuthanová Trsková, Eliška; Bína, David; Santabarbara, Stefano; Sobotka, Roman; Kaňa, Radek; Belgio, Erica (Physiologia plantarum, 2019)
In the present paper, we report an improved method combining sucrose density gradient with ion-exchange chromatography for the isolation of pure chlorophyll a/c antenna proteins from the model cryptophytic alga Rhodomonas salina. Antennas were used for in vitro quenching experiments in the absence of xanthophylls, showing that protein aggregation is a plausible mechanism behind non-photochemical quenching in R. salina. From sucrose gradient, it was also possible to purify a functional photosystem I supercomplex, which was in turn characterized by steady-state and time-resolved fluorescence spectroscopy. R. salina photosystem I showed a remarkably fast photochemical trapping rate, similar to what recently reported for other red clade algae such as Chromera velia and Phaeodactylum tricornutum. The method reported therefore may also be suitable for other still partially unexplored algae, such as cryptophytes.
Keywords: Chlorophyll; fluorescenční spektrometrie; Spectrometry, Fluorescence; Photosystem I Protein Complex; xanthofyly; chlorofyl; Xanthophylls; Rhodophyta; fotosystém I (proteinový komplex)